NLRP3 Inflammasome Mediates Immune-Stromal Interactions in Vasculitis. Issue 9 (15th October 2021) - Porritt, Rebecca A.; Zemmour, David; Abe, Masanori; Lee, Youngho; Narayanan, Meena; Carvalho, Thacyana T.; Gomez, Angela C.; Martinon, Daisy; Santiskulvong, Chintda; Fishbein, Michael C.; Chen, Shuang; Crother, Timothy R.; et al.
Abstract : Rationale: NLRP3 (NLR family pyrin domain containing 3) activation and IL-1β (interleukin-1β) production are implicated in Kawasaki disease (KD) pathogenesis; however, a detailed and complete characterization of the molecular networks and cellular subsets involved in the development of cardiovascular lesions is still lacking. Objective: Here, in a murine model of KD vasculitis, we used single-cell RNA sequencing and spatial transcriptomics to determine the cellular landscape of inflamed vascular tissues. Methods and Results: We observe infiltrations of innate and adaptive immune cells in murine KD cardiovascular lesions, associated with increased expression of Nlrp3 and Il1b . Monocytes, macrophages, and dendritic cells were the main sources of IL-1β, whereas fibroblasts and vascular smooth muscle cells (VSMCs) expressed high levels of IL-1 receptor. VSMCs type 1 surrounding the inflamed coronary artery undergo a phenotype switch to become VSMCs type 2, which are characterized by gene expression changes associated with decreased contraction and enhanced migration and proliferation. Genetic inhibition of IL-1β signaling on VSMCs efficiently attenuated the VSMCs type 2 phenotypic switch and the development of cardiovascular lesions during murine KD vasculitis. In addition, pharmacological inhibition of NLRP3 prevented the development of cardiovascular inflammation. Conclusions: Our studies unravel the cellular diversity involved in IL-1β production and signaling in murine KD cardiovascular lesions and provide the rationale for therapeutic strategies targeting NLRP3 to inhibit cardiovascular lesions associated with KD. Abstract : Supplemental Digital Content is available in the text.